“IT’S ALL IN THE MIND”: AN ADLERIAN STUDY OF THE PSYCHE OF THE CHARACTERS IN SARNATH BANERJEE’S GRAPHIC NOVEL CORRIDOR - Murmu, Ashish; Mishra, Binod (ShodhKosh: Journal of Visual and Performing Arts, 2025)
This study will focus on the main characters from Sarnath Banerjee’s graphic novel "Corridor" (2004) and analyze their personalities’ significant facets. The tale depicts the routine urban existence in the city of Delhi. Banerjee’s use of the non-linear fragmented form of storytelling, in which a short fiction (or stories) is inserted into a longer narrative at multiple levels, is an example of a technique known as "a story inside a story." Thus, this research examines Adler’s five central postulates through the in-depth textual reading of this novel using the theoretical framework of Adler’s "Individual Psychology" and the descriptive-analytical techniques. Furthermore, the critical analysis reveals that the novel’s protagonists always seek a perfect solution to improve their imperfect life structure. We find that five postulates of Individual Psychology, including (i) Inferiority Complex, (ii) Fictional Finalism, and (iii) Striving for Superiority, are particularly well suited to each of the individual characters in the study of this novel. The comparative research displays not only the distinctive identities and personalities of Delhi’s city and its destabilized monotonous life but also paves the way to understand psychology through graphic novels.